The Human Rights Discourse in Health (19 key statements) - Claudio Schuftan (Social Medicine Publication Group, 2022)
Food for a flagrantly violated thought. Meaning of the human rights discourse in health: The revived interest in a HR-based approach to development and to our work in health is well justified and an advantage over our current approach. Human Rights (HR) - and the Right to Health - have a particular concern about those who are disadvantaged, marginal and living in poverty.  Widespread unsatisfied health needs - primarily of the poor who lack economic access to health services (and are now faced with widespread fee-for-service charges) - represent flagrant violations of the rights of a majority of people.